Morphological Characteristics of Neuronal Death After Experimental Subarachnoid Hemorrhage in Mice Using Double Immunoenzymatic Technique. (December 2019) - Nakano, Fumi; Liu, Lei; Kawakita, Fumihiro; Kanamaru, Hideki; Nakatsuka, Yoshinari; Nishikawa, Hirofumi; Okada, Takeshi; Shiba, Masato; Suzuki, Hidenori
Subarachnoid hemorrhage (SAH) is a devastating disease. Neuronal death is an important pathophysiology in the acute phase of SAH, but the histopathological features of dying neurons have been poorly studied. Using several staining methods including terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and microtubule-associated protein 2 (MAP-2) double immunolabeling, we investigated the morphological changes of nucleus and cytoskeleton in neurons and sought susceptible areas to neuronal death in filament perforation SAH mice under light microscope. TUNEL and MAP-2 double immunolabeling clearly showed morphological features of shrunken cytoplasm and sometimes curl-like fibers in dying neurons, besides nuclear abnormalities. More dying neurons were detected in the moderate SAH group than in the mild SAH group, and the temporal base cortex was the most susceptible area to neuronal death with deoxyribonucleic acid (DNA) damage among the cerebral cortices and hippocampus at 24 hr after SAH ( p <0.01, ANOVA). Lesser hippocampal neuronal death was observed at 24 hr, but neuronal death was significantly increased in the CA1 region at 7 days after SAH ( p <0.05, unpaired t- test). Using TUNEL and MAP-2 double immunolabeling, morphological features of not only the nucleus but also the cytoplasm in post-SAH neuronal death with DNA damage can be observed in detail under light microscope: